Restrictions of fixed term employment contracts: evidence from a German reform - Brüll, Eduard (Discussion paper, 2019)
This paper examines the impact of legal restrictions on fixed-term contracts on employment, wages and the careers of labour market entrants. Specifically, I analyse a 2001 German reform that made it more difficult for establishments that are not subject to employment protection to hire workers on fixed-term contracts. Using a Difference-in-Differences approach, which compares establishments subject to employment protection with those that are not both before and after the reform, I find that the reform has reduced the use of fixed-term contracts, but has not markedly changed net employment. However, the reform has had positive effects on the career stability of post-reform labour market entrants.